2014
DOI: 10.1111/mmi.12869
|View full text |Cite
|
Sign up to set email alerts
|

BcNoxD, a putative ER protein, is a new component of the NADPH oxidase complex in Botrytis cinerea

Abstract: SummaryNADPH oxidases (Nox) are major enzymatic producer of reactive oxygen species (ROS). In fungi these multi-enzyme complexes are involved in sexual differentiation and pathogenicity. However, in contrast to mammalian systems, the composition and recruitment of the fungal Nox complexes are unresolved. Here we introduce a new Nox component, the membrane protein NoxD in the grey mold fungus Botrytis cinerea. It has high homology to the ER protein Pro41 from Sordaria macrospora, similar functions to the cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 78 publications
3
87
0
Order By: Relevance
“…Although many aspects of their function in fungi are still unknown, there is increasing evidence of structural/functional homologies between Nox complexes in mammals and fungi, despite of the evolutionary distance. For example, homologs of the regulatory subunit (p67phox/NoxR), the catalytic subunit (gp91phox/Nox1/2 or NoxA/B) as well as other regulatory compounds (p22phox/ NoxD) (Cano-Dominguez et al, 2008;Egan et al, 2007;Lacaze et al, 2015;Lara-Ortiz et al, 2003;Malagnac et al, 2004;Segmueller et al, 2008;Semighini and Harris, 2008;Siegmund et al, 2013Siegmund et al, , 2015 have been already identified and characterized. To handle elevated levels of ROS, eukaryotic cells have evolved scavenging systems to establish and maintain an equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Although many aspects of their function in fungi are still unknown, there is increasing evidence of structural/functional homologies between Nox complexes in mammals and fungi, despite of the evolutionary distance. For example, homologs of the regulatory subunit (p67phox/NoxR), the catalytic subunit (gp91phox/Nox1/2 or NoxA/B) as well as other regulatory compounds (p22phox/ NoxD) (Cano-Dominguez et al, 2008;Egan et al, 2007;Lacaze et al, 2015;Lara-Ortiz et al, 2003;Malagnac et al, 2004;Segmueller et al, 2008;Semighini and Harris, 2008;Siegmund et al, 2013Siegmund et al, , 2015 have been already identified and characterized. To handle elevated levels of ROS, eukaryotic cells have evolved scavenging systems to establish and maintain an equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…In M. oryzae, Nox1 and NoxD interact-but participate differently in septinmediated cytoskeleton organization-indicating the fungal NADPH oxidase complex is dynamic (Galhano et al, 2017). Interestingly, B. cinerea, but not M. oryzae ΔnoxD mutants, had growth defects in the presence of oxidative stress, suggesting a diversification of NoxD function and differences in ROS signaling between fungi (Galhano et al, 2017;Siegmund et al, 2015). In M. oryzae, NOXD gene expression is dependent on a Zn(II) 2 Cys 6 family transcription factor that also interacts with machinery of the Map kinase signaling cascade (Galhano et al, 2017).…”
Section: Nadph Oxidase Complexesmentioning
confidence: 99%
“…Fungi possess three Nox enzymes; NoxA (also known as Nox1) and NoxB (also known as Nox2) are homologous of the gp91 phox catalytic subunit while NoxC carries a Ca 2+ -binding EF hand and is similar to mammalian Nox5 (Aguirre et al, 2005;Heller and Tudzynski, 2011;Ryder et al, 2013). Nox requires adapter proteins for function, yet the homolog of the adaptor protein p22 phox (NoxD) has only recently been characterized in Podospora anserina, Botrytis cinerea and Magnaporthe oryzae (Lacaze et al, 2015;Scott, 2015;Siegmund et al, 2015;Galhano et al, 2017). NoxD acts with Nox1 in P. anserina and NoxA in B. cinerea, and NoxD deletion strains in these fungi are phenotypically identical to the respective Nox1/NoxA mutant, suggesting they act together (Lacaze et al, 2015;Scott, 2015;Siegmund et al, 2015).…”
Section: Nadph Oxidase Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The PaNox2 complex and the PaMpk2 MAP kinase are important for the initial reorientation phase, while the PaNox1 complex is involved in the generation of the needle-like hyphae. The Nox1, Nox2 and Mpk2 orthologues are also involved in the formation of appressoria or appressorium-like structures in phytopathogenic fungi, such as Magnaporthe oryzae (Egan et al, 2007) and Botrytis cinerea (Segmuller et al, 2008;Siegmund et al, 2015). In these species, the Nox1, Nox2 and Mpk2 mutants are strikingly blocked at the same stage, suggesting that the machinery used to differentiate the penetration structures is highly conserved, at least in the Ascomycota.…”
Section: Biomass Colonization Mechanismsmentioning
confidence: 96%